TANTANGAN DAN SOLUSI PENGUATAN NILAI PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR DI ERA DIGITAL - Nurhayani; Yakobus Ndona; Daulat Saragi (STKIP Subang, 2025)
This study aims to examine various challenges and find solutions to instilling character education in the digital era. The research was conducted using qualitative methods through a naturalistic approach. Data collection techniques included surveys, interviews, observations, and literature studies. The analysis process was conducted based on Creswell's six stages of analysis. The results show that digital development presents two sides: challenges and opportunities in strengthening character education. The digital era has proven capable of supporting the implementation of character education, but at the same time, it raises ethical issues that must be managed appropriately. Challenges faced include maintaining a balanced use of technology, issues of security and safety in cyberspace, cases of digital bullying, sexting practices, copyright infringement and plagiarism. The role of education policymakers is crucial in designing consistent and sustainable digital-based character learning strategies. However, implementation faces obstacles such as the influence of global culture, teachers' limited understanding of Pancasila, and a lack of supporting facilities. Therefore, collaboration between the government, schools, and the community is necessary. This study emphasizes that internalizing Pancasila values in the digital era must be carried out through a comprehensive and sustainable strategy to be able to meet the challenges of technological development.